Kedudukan Anak Luar Nikah dalam Hukum Perkawinan - Siregar, Dahris (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
Children born outside of marriage provide a dilemma in day-to-day living, yet there are also others who view this as the standard. Even though they are hated and denigrated, they nevertheless have little civil and welfare rights since they are illegitimate children, meaning they have no legal connection to their father. Furthermore, because he has no nasab link or legal tie with his mother, who gave birth to him, the boy is not eligible to receive money or inheritance from his father. Unmarried children therefore have a lot of rights and responsibilities with their parents. This research aims to investigate the legal protection of children born outside of marriage in the aftermath of the Constitutional Court's Decision No.46/PUU-VIII/2010. It does this by learning about their legal status under Islamic law, Law No. 1 of 1974, and the Civil Code. Adopting a normative legal perspective, the research is carried out deductively by looking at the articles of law that govern the problem to be studied. Then, this study looks at how one law relates to another and how it is applied in practice. The study's findings demonstrated that illegitimate children only had cordial relationships with their mother and relatives. As a consequence, children born outside of marriage are considered illegitimate under the Civil Code but may be recognized, but they are considered illegitimate under Law No. 1 of 1974 and KHI. This is in line with the Constitutional Court's ruling No. 46/PUU-VIII/2010 on the recognition of such children.